HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP PENCEGAHAN DEMAM BERDARAH DENGUE DENGAN 3M PLUS DI WILAYAH KERJA PUSKESMAS KOTA PARIAMAN - SYAHRUL, SYAHRUL; ZAYANI, NOFRI; YUNTARISA, ATIKA PRADANA; ELIZA, AIDA (As-Shiha : JOURNAL OF MEDICAL RESEARCH, 2024)
Dengue Hemorrhagic Fever (DHF) is a health problem in tropical countries. The World Health Organization (WHO) in 2023 reported that an unexpected spike in dengue fever cases resulted in the highest number in history, namely more than 6.5 million cases with more than 7,300 deaths. The prevalence of DHF in West Sumatra in 2020 was 292 cases. The purpose of the study was to determine the Relationship between Knowledge and Community Attitudes Towards DHF Prevention with 3M Plus in the Pariaman Health Center work area. The research method used quantitative research with a descriptive analytical design with a Cross Sectional Study approach. The study was conducted in Kp. Jawa II, Central Pariaman. The research sample was 85 heads of families. Sampling was done by acidential sampling. Statistical tests using Chi Square. The results of the study showed that the majority of the community (69.4%) had low knowledge, (56.5%) had negative attitudes, and (65.9%) the community was low in preventing DHF with 3M Plus. There is a significant relationship between knowledge of dengue prevention and 3M Plus showing p value = 0.000. There is a significant relationship between attitude and dengue prevention with 3M Plus showing p value = 0.000.